CONTEMPORARY DEMOGRAPHIC CHANGES IN SETELLMENTS ALONG THE ADMINISTRATIVE LINE IN SERBIA TOWARDS AUTONOMOUS PROVINCE OF KOSOVO AND METOHIJA - Vukoičić, Danijela; Nikolić, Milena; Raičević, Jelena (Bulletin of Natural Sciences Research, 2016)
The settlements along the administrative line in Serbia towards Kosovo and Metohija had a very turbulent demographic changes in the past. These changes have influenced the present. In this paper we investigated the depopulation process of this area which is intensified with the political instability, social and economic changes. The main goal of this research was to analyze the causes and effects in the reduction of the number of inhabitants, as well as the possibility of revitalizing the rural settlements of a given area. To obtain the desired results, we analyzed the existing literature and statistical data, used comparative and historical methods as well as implemented the field surveys. The application of the SWOT analysis to the researched area have showed us the strength, weakness, opportunities, and threats that can effect the process of revitalization of the village.